Development and evaluation of an Acyclovir-loaded cod liver oil nanoemulsion for enhanced anticancer activity - Hadil Faris Alotaibi (Journal of Taibah University for Science)
This study investigates the anticancer potential of an Acyclovir-loaded cod liver oil nanoemulsion, combining the health benefits of cod liver oil with the therapeutic effects of Acyclovir, a drug traditionally used for treating viral infections but repurposed here for cancer therapy. The nanoemulsion demonstrated improved solubility of Acyclovir, with optimal physical properties conducive to effective drug delivery. Key findings include a particle size of 114 ± 5 nm, a zeta potential of −7 ± 3 mV and a high drug content of 98.5 ± 1.25%, with maintained stability over three months. Notably, the nanoemulsion induced significant apoptotic cell death and cell cycle arrest in the G2 phase across all tested cancer cell lines, highlighting its potent anticancer activity.